Analysis of Students’ Reflections and Ideation in an Online Graduate Ecology Course - Habito, Consuelo dL.; Serrano, Joane V.; Ealdama, Susan Janette G. (International Journal on Open and Distance e-Learning, 2018)
Plastics have become one of the biggest environmental and societal problems that affect land, oceans, waterways, living organisms, and humans. The three countries that have the largest contributions to plastic wastes in the oceans are China, Indonesia, and the Philippines. (Jambeck et al., 2015). These countries are identified as rapidly developing countries that are engaging in investments from wealthier foreign investors. “Megacities” in these developing countries have populations exceeding 10 million (Tibbetts, 2015). Among the factors for the continued use of plastics despite the advocacies of various sectors are the mindset and knowledge gap that plastics are easily recycled (Miller, Soulliere, Sawyer-Beaulieu, Tseng, and Tam, 2014) and the need for education, awareness, sharing of educational resources on reducing plastics, and working closely with industries producing plastics (Jambeck et al., 2017). Hence, educational institutions all over the world must integrate in their lessons and in their class activities various ways on how to help stop the worldwide problem of plastic pollution. Students and their generation at large are seen as having the greatest capacity of enacting environmental advocacies. The aim of this study was to explore a teaching approach using the reflections and ideation of the ENRM 223 students about the plastic pollution-solution issue. This study also examined how reflexive practice can bring out ideas and possible strategies and practical actions for environmental advocacy. The study focused on two major questions: 1) How did the students apply concepts from the course in their reflections on the video in terms of authorship, purpose, economics, impact, response, content, techniques, interpretation, and context? and 2) How did the video’s message influence the students’ ideations and turn these into practical applications? The analysis of the responses was intended to contribute toward theory-building on effective long-term approaches to strengthening environmental advocacy strategies in online teaching and learning. Recommendations include identifying the mix of individual and contextual factors that best address the need; evaluating the intervention and verifying the strategy; and tightening the link in strategic environmental advocacy planning, program design, and program implementation in order to achieve long-term sustainable environmental outcomes.